The incidence and mortality of lung cancer in China: a trend analysis and comparison with G20 based on the Global Burden of Disease Study 2019 - Long, Jianhai; Zhai, Mimi; Jiang, Qin; Li, Jiyang; Xu, Cixian; Chen, Duo (Frontiers in Oncology, 2023)
Background Lung cancer is a significant health concern in China. There is limited available data of its burden and trends. This study aims to evaluate the trends of lung cancer across different age groups and genders in China and the Group of Twenty (G20) countries, explore the risk factors, and predict the future trends over a 20-year period. Methods The data were obtained from the GBD study 2019. The number of cases, age standardized rate (ASR), and average annual percentage changes (AAPC) were used to estimate the trend in lung cancer by age, gender, region and risk factor. The trend of lung cancer was predicted by autoregressive integrated moving average (ARIMA) model by the “xtarimau” command. The joinpoint regression analysis was conducted to identify periods with the highest changes in incidence and mortality. Additionally, the relationship between AAPCs and socio-demographic index (SDI) was explored. Results From 1990 to 2019, both the incidence and mortality of lung cancer in China and G20 significantly increased, with China experiencing a higher rate of increase. The years with the highest increase in incidence of lung cancer in China were 1998-2004 and 2007-2010. Among the G20 countries, the AAPC in incidence and mortality of lung cancer in the Republic of Korea was the highest, followed closely by China. Although India exhibited similarities, its AAPC in lung cancer incidence and mortality rates was lower than that of China. The prediction showed that the incidence in China will continue to increase. In terms of risk factors, smoking was the leading attributable cause of mortality in all countries, followed by occupational risk and ambient particulate matter pollution. Notably, smoking in China exhibited the largest increase among the G20 countries, with ambient particulate matter pollution ranking second. Conclusion Lung cancer is a serious public health concern in China, with smoking and environmental particulate pollution identified as the most important risk factors. The incidence and mortality rates are expected to continue to increase, which places higher demands on China’s lung cancer prevention and control strategies. It is urgent to tailor intervention measures targeting smoking and environmental pollution to contain the burden of lung cancer.